Crosstalk between oral and general health status in e-smokers. Issue 49 (December 2016) - Tatullo, Marco; Gentile, Stefano; Paduano, Francesco; Santacroce, Luigi; Marrelli, Massimo
Abstract : Abstract: Electronic cigarette (e-cigarette) simulates the act of tobacco smoking by vaporizing a mixture of propylene glycol, nicotine, and flavoring agents. e-cigarette has been proposed as a product able to aid to stop smoking. The aim of the study is to verify the clinical variations of periodontal health induced by e-cigarettes use and, moreover, to investigate about the awareness of the e-smokers about their health variations and about their hypothetical need to turn back to smoke combustible cigarettes. This clinical observational pilot study involved 110 out of 350 smokers, who switched to e-cigarette. Patients were subjected to oral examinations. A questionnaire to self-assess the variations of some parameters of general health, and to self-assess the need to smoke combustible cigarettes, was distributed to such subjects involved in the study. At the end of the study, we registered a progressive improvement in the periodontal indexes, as well as in the general health perception. Finally, many patients reported an interesting reduction in the need to smoke. In the light of this pilot study, the e-cigarette can be considered as a valuable alternative to tobacco cigarettes, but with a positive impact on periodontal and general health status.